Glycerol Enhances the Antifungal Activity of Dairy Propionibacteria - Helena Lind; Anders Broberg; Karin Jacobsson; Hans Jonsson; Johan Schnürer (International Journal of Microbiology)
Dairy propionibacteria are widely used in starter cultures for Swiss type cheese. These bacteria can ferment glucose, lactic acid, and glycerol into propionic acid, acetic acid, and carbon dioxide. This research examined the antifungal effect of dairy propionibacteria when glycerol was used as carbon source for bacterial growth. Five type strains of propionibacteria were tested against the yeast Rhodotorula mucilaginosa and the molds Penicillium commune and Penicillium roqueforti. The conversion of 13C glycerol by Propionibacterium jensenii was followed with nuclear magnetic resonance. In a dual culture assay, the degree of inhibition of the molds was strongly enhanced by an increase in glycerol concentrations, while the yeast was less affected. In broth cultures, decreased pH in glycerol medium was probably responsible for the complete inhibition of the indicator fungi. NMR spectra of the glycerol conversion confirmed that propionic acid was the dominant metabolite. Based on the results obtained, the increased antifungal effect seen by glycerol addition to cultures of propionibacteria is due to the production of propionic acid and pH reduction of the medium.